2009
DOI: 10.1002/aic.12097
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transverse rotating magnetic field on enhancement of solid dissolution process

Abstract: in Wiley InterScience (www.interscience.wiley.com).The main objective of this work is to study the effect of transverse rotating magnetic field (TRMF) on the enhancement of solid dissolution process in the novel type reactor (TRMFR). The application of magnetically driven fluidization (MDF with homogeneous and heterogeneous systems) on mass transfer process is presented. A study of the effect of ferromagnetic particles content on solid-liquid mass transfer has been made. The experimental investigations are pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The SMF is characterized by steady direction, flow rate and strength (thus a frequency of 0 Hz) (Shanmugapriya et al, 2012). In contrast to SMF, the RMF (as time varying magnetic field) reverses their direction at a regular frequency and this kind of field rotates around the generator axis with the constant angular frequency (Rakoczy & Masiuk, 2010). In the present study the frequency was equal to 50 Hz (it was equal to the frequency of the alternating current which supplies the windings).…”
Section: Discussionmentioning
confidence: 94%
“…The SMF is characterized by steady direction, flow rate and strength (thus a frequency of 0 Hz) (Shanmugapriya et al, 2012). In contrast to SMF, the RMF (as time varying magnetic field) reverses their direction at a regular frequency and this kind of field rotates around the generator axis with the constant angular frequency (Rakoczy & Masiuk, 2010). In the present study the frequency was equal to 50 Hz (it was equal to the frequency of the alternating current which supplies the windings).…”
Section: Discussionmentioning
confidence: 94%
“…Another effect is to increase the dissolution of iron. Rakoczy reported that rotating magnetic field enhances solid dissolution process [19,20]. MF can also influence the lifetime of radicals by inhibiting their recombination reactions through the interaction with electron spins [21].…”
Section: Introductionmentioning
confidence: 98%
“…After finishing the cycle of dissolving, the agitator was stopped, and then the loss of mass had been read on electronic scale and concentration of NaCl (electrical conductivity) in the mixer as well. This connection is given by a calibration curve, showing the dependence of the relative mass concentration of NaCl on the electrical conductivity (Rakoczy & Masiuk, 2010). (44) is useful to generalize the experimental data in this work for the whole region of the reciprocating Reynolds number without the break of the correlating graphical line.…”
Section: Methodsmentioning
confidence: 97%
“…The influence of TRMF on mass-transfer process is manifested by the magnetic force defined as the divergence of Maxwell's stress tensor and expressed by the following relation (Rakoczy & Masiuk, 2010) V -liquid volume exposed to TRMF, m 3 ; μ m -magnetic permeability, kg·m·A -2 ·s -2 .…”
Section: Influence Of Transverse Rotating Magnetic Field (Trmf) On Mamentioning
confidence: 99%